MOUSE AND HUMAN EMBRYONIC STEM CELLS - A. G. Menzorov (Вавиловский журнал генетики и селекции)
This mini review is focused on the current state in the field of mouse and human embryonic stem (ES) cell biology. Methods of ES cell derivation, pluripotency assessment and problems associated with long term cultivating in vitro are discussed. Attention is given to some unresolved questions of ES cell biology and prospects of ES cells in cell therapy.